Risk Assessment in Specialised Home gardens of Kerala - C, Sreelakshmi (Journal of Extension Education, 2018)
Home gardens have emerged as the best agricultural production system in Kerala due to limiting land availability and the shrinking operational land unit. Time and act of commercialization have transformed the homegardens to more diversified and specialized home gardens. A critical study of risks in the specialized homegarden production systems is the need of the hour to enhance its productivity. This paper analyses the various risk factors in home gardens.